Digital Video Stabilization: Algorithms and Evaluation - Souza, Marcos Roberto e; Pedrini, Helio (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2019)
Several devices have allowed the acquisition and editing ofvideos in various circumstances, such as digital cameras, smartphones and other mobile devices. However, the use ofcameras under adverse conditions usually results in non-precise motion and occurrence of shaking, which may compromise the stability of the obtained videos. To overcome such problem, digital stabiliza- tion aims to correct camera motion oscillations that occur in the acquisition process, particularly when the cameras are mobile and handled in adverse con- ditions, through software techniques, without the use of specific hardware, to enhance visual quality either with the intention of enhancing human percep- tion or improving final applications, such as detection and tracking of objects. This is important in order to avoid hardware cost and indispensable for videos already recorded. This work proposed three methods to perform digital video stabilization and two other techniques to evaluate video stabilization quality. 1.